PROSES BERAGAMA AHMADIYAH DALAM PERSPEKTIF ALFRED NORTH WHITEHEAD - Syahrul Kirom (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2016)
This article seeks to describe and explain the presence of the Doctrine of Ahmadiyah in Indonesia. The existence of Ahmadiyah in Indonesia is still considered getting opposition from Muslims in part because some of the teachings of Ahmadiyah is not in accordance with Islam, including about his Prophet. But also the people of the Ahmadiyya consider it still recognizes as the religion of Islam. Writing this paper uses descriptive qualitative method, using an analytical approach, the theory used to analyze the Ahmadiyah issue is of the thought of Alfred North Whitehead. Especially on Ontology from Whitehead thought in understanding the process of one's religion. Ontology Whitehead, who starts from entities actual, whose presence as an actual first as the process of the emergence of the Ahmadiyya in understanding the prophet, Mirzam Ghulam, which would also have an impact on the process kebertuhanannya and own religion and religious experience of adherents of Ahmadiyah in Indonesia. Therefore, the Ahmadiyya, an Islamic religion which is continuously preparing dogma and doctrines into a coherent system, logical, adequate and applicable. Islamic religion that developed in real Ahmadiyah religious splinter flow in the process, something that is "becoming". Thus, Muslims must know, understand and appreciate the values of the differences Ahmadiyah teachings of the Islamic religion in general and it's part of the philosophy of the process. Whitehead also said that every experience (experience) that man is bagiana of a change and the human process that is different from the others, to create a "novelty", with the actual units. It further confirms that the thought Whitehead would like to emphasize the plurality or plurality of human reality in finding keberagamaaannya. The author can assert that the existence of the Ahmadiyya in Indonesia as a religious sect that is the religious experience of each of each man to "be 'good and create creativity and uniqueness transcendentally.